CONTRIBUTION TO THEORETICAL AND PRACTICAL DEVELOPMENT OF MINING PROJECTING - Jerko Nuić; Andrija Mikulić (Rudarsko-geološko-naftni Zbornik, 1995)
Mining project is a directive and guiding principle of all activities in practice and it is generaly not evaluated corresponding wilh its significance. There is a risk present in project grounds. Minimun investigation is prescribed. The acccpted legislature widens the number of project-performers. Verification procedure does not improve enough the quality of performance. Project control is neither an obligation nor a practice. The article discusses particularly the importance of projecting, significance of project grounds and introduces the treshold of explorability as a mining-geological-economic criterium, A project task should stimulate the creativity of project-performers. Revision of the project should be made more severe and oriented to its essential directives. The intoduction of project control is justified (the paper is published in Croatian).